Our secret constitution : how Lincoln redefined American democracy - Fletcher, George P. (Oxford University Press, 2001)
Americans hate and distrust their government, but, at the same time, love and trust their government. These contradictory attitudes are resolved by Fletcher's novel interpretation of constitutional history. He says that the US has 2 constitutions - one catering to freedom and fear, the other to the need for security and social justice.